Neurological Manifestations of H. Pylori Infection - Muhammad Khan Malik, Khalil Ahmed, Muhammad Azeem, Nasar Iqbal Ranjha (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Helicobacter pylori are a gram negative bacterium that spreads infection in nearly half of a population. It lives in gastric conditions and causes various gastric disorders. Besides, h.pylori infection affects other organs of the body and causes many disorders including ischemic stroke, Parkinson’s disease, Alzheimer’s disorder, migraine headache and multiple sclerosis. Material and Method: A cross-sectional study was conducted on H.pylori patients through convenient sampling. Patients were admitted to hospital with clinical symptoms of disease and with neurological manifestations. Their co morbid factors were also identified along with laboratory investigations Result: Among the 276 hospitalized patients 138 were males and 138 were females with age of 60-80.Seventy-two with diabetes mellitus, 45 had ischemic heart disease, 57 had hypertension. Multiple neurological disorders including Parkinson’s disorder, Alzheimer’s, ischemic stroke, multiple sclerosis, migraine are present in patients of h.pylori infection. Conclusion: H. pylori infection has been associated with the development and progression of neurological conditions, basically by inducing systemic inflammation, molecular belittlement , and interference with the absorption of drugs. Eradication of h.pylori infection lessens the threat of many neurological conditions.